Dinamika Indeks Kedalaman dan Keparahan Kemiskinan di Nusa Tenggara Barat - Ibrahim Ibrahim (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Poverty is a challenge in socio-economic development in West Nusa Tenggara (NTB). Its impact on the social welfare of the community Poverty Depth Index and Severity Index. This study aims to analyze the Poverty Depth Index and Poverty Severity Index in NTB. The research method uses a descriptive quantitative approach. The data source uses secondary data from the Central Statistics Agency (BPS) of NTB for the period 2010–2024. The analysis uses qualitative descriptive. The results of the study show that North Lombok Regency has a depth level of 6.08 in 2022 and the highest poverty severity reaching 1.97 in 2022. This condition is influenced by factors of geographic access, infrastructure and earthquake and Covid-19 disasters. Mataram City has the lowest depth index reaching 0.93 in 2021 and a severity index reaching 0.19 in 2021. Supporting factors include easy access to education, employment and health services and the existence of economic disparities between regions in NTB is quite high. This finding is important in a holistic approach to formulating data-based poverty alleviation policies.